Analysis of Rewetting Time and Temperature Distributions During Cooling Process in Vertical Rectangular Narrow - Bagus Catrawedarma, IGN.; Indarto, Indarto; Juarsa, Mulya (Jurnal Energi Dan Manufaktur; Vol 6 No 2 (2013): Oktober 2013)
Abstract Cooling process to analyze effect of gap size to rewetting time and temperature distributions were studied from transient temperature of surface plate. It as result of experiment using two vertical plate with the initial temperature about 600°C. Debit and temperature of cooling water are 0,09 L/s and saturated temperature. The gap sizes were changed from 1 mm, 2 mm, and 3 mm. As the results showed that the smaller the gap size, the longer the rewetting time. Pattern of temperature distribution is similar at initial condition for all of gap sizes and the smaller the gap sizes, the longer the time of decreasing temperature. Keywords: Cooling process, rewetting time, temperature distribution. Abstrak Proses pendinginan untuk menganalisa pengaruh ukuran celah terhadap waktu pembasahan dan distribusi temperatur diamati dari transient temperatur permukaan plat. Penelitian dilakukan menggunakan dua plat vertikal dengan temperatur awal 6000C. Debit dan temperatur air pendingin adalah 0,09 L/s dan temperatur jenuh. Ukuran celah divariasikan dari 1 mm, 2 mm dan 3 mm. Hasil penelitian menunjukkan bahwa semakin kecil ukuran celah semakin panjang waktu rewetting. Pola distribusi temperaursama pada kondisi awal untuk semua ukuran celah, semakin kecil ukuran celah semakin panjang waktu untuk penurunan temperatur. Kata kunci: Proses pendinginan, rewetting time, distribusi temperatur
Keywords: Cooling process, rewetting time, temperature distribution